Multi-Biofunctional Properties of Phytofabricated Selenium Nanoparticles From Carica papaya Fruit Extract: Antioxidant, Antimicrobial, Antimycotoxin, Anticancer, and Biocompatibility - Vundela, Swetha Reddy; Kalagatur, Naveen Kumar; Nagaraj, Anusuya; Kadirvelu, Krishna; Chandranayaka, Siddaiah; Kondapalli, Kasturi; Hashem, Abeer; Abd_Allah, Elsayed Fathi; Poda, Sudhakar (Frontiers in Microbiology, 2022)
The study focused on phytofabrication of selenium nanoparticles (SeNPs) from Carica papaya extract and exploration of their multi-biofunctional features. Total phenolics and flavonoids of C. papaya fruit extract were determined as 23.30 ± 1.88 mg gallic acid equivalents and 19.21 ± 0.44 mg quercetin equivalents per g, respectively, which suggested that C. papaya fruit extract could be a competitive reducing and stabilizing agent during phytofabrication of nanoparticles. UV-Vis and FTIR spectroscopy showed the formation of SeNPs from sodium selenite, which could be related to the reducing and stabilizing activities of C. papaya fruit extract. The SeNPs found to be stable with a Zeta potential of -32 mV. The average hydrodynamic size of SeNPs was found as 159 nm by the DLS. The SeNPs showed a broader XRD pattern with no sharp Bragg's peaks and found amorphous. The SEM showed that SeNPs were spherical in shape and EDX pattern showed that SeNPs were made up of Se (71.81%), C (11.41%), and O (14.88%). The HR-TEM picture showed that SeNPs were spherical in morphology and have a size range of 101 – 137 nm. The SeNPs exhibited potent antioxidant activity and their EC50 values (effective concentration required to inhibit 50% of radicals) were 45.65 ± 2.01 and 43.06 ± 3.80 µg/mL in DPPH and ABTS assays, respectively. The antimicrobial action of SeNPs was found as a broad spectrum and suppressed microbial pathogens in the ascending order: fungi > Gram-positive bacteria > Gram-negative bacteria. The SeNPs have been demonstrated to reduce the growth and ochratoxin A (OTA) of mycotoxigenic Aspergillus ochraceous and Penicillium verrucosum at 40 µg/mL in broth culture, which is noteworthy. The SeNPs reduced cancer cells proliferation (RAW 264.7, Caco-2, MCF-7, and IMR-32) more preferentially than normal cells (Vero), found highly biocompatible. The lower doses of SeNPs (up to 50 µg/mL) were shown to be less toxic and did not cause death in Danio rerio (Zebrafish) embryos, implying that lower doses of SeNPs could be beneficial for biological purposes. The study concluded that phytofabricated SeNPs have multiple biofunctional properties, including antioxidant, antimicrobial, antimycotoxin, and anticancer activities, as well as high biocompatibility.